Working Memory Maintenance Modulates Serial Dependence Effects of Perceived Emotional Expression - Mei, Gaoxing; Chen, Shiyu; Dong, Bo (Frontiers in Psychology, 2019)
The stability of face perception is vital in interpersonal interaction. Recent studies have revealed the mechanism of the stability in the perception of stable attributes of faces (such as facial identity) by serial dependence, a phenomenon in which perception of current stimuli is pulled toward recently viewed stimuli. However, whether serial dependence of perceived emotional expression (a changeable attribute of faces) could exist remains controversial, and its exact nature has not yet been examined. To address these issues, we used the methods of constant stimuli and two-interval forced choice tasks in the three psychophysical experiments. Participants compared two successive facial expressions selected from a continuum with 50 morphed faces ranging from sad to happy. Experiment 1a and 1b showed that perceived facial expression was pulled toward previously seen facial expressions (i.e., a significant serial dependence effect), independent of response instructions. Furthermore, a stronger serial dependence effect was found when the first facial expression was retained in working memory for a longer delay duration (Experiment 2), and yet a weaker serial dependence effect was observed when a longer delay between decision and response was performed (Experiment 3). These findings indicate that serial dependence facilitates the stability of facial expression perception, and is modulated by working memory representations.